Corporate communication a guide to theory and practice - Cornelissen, Joep; Alfonso, Delia (Los Angeles, Calif. SAGE, 2014)
Used by nearly 20,000 students in over 50 different countries on courses in Corporate Communication, Organizational Communication, PR and Marketing Communications and as an invaluable source for reflective practitioners, the new fourth edition has been updated to include topics such as the new media environment, CSR standards and corporate citizenship whilst retaining its practical yet strong theoretical approach.
Part I. Introduction -- Chapter 1. Defining corporate communication -- Chapter 2. Corporate communication in contemporary organizations -- Chapter 3. Corporate communication in a changing media environment -- Part II. Conceptual foundations -- Chapter 4. Stakeholder management and communication -- Chapter 5. Corporate identity, branding and corporate reputation -- Part III. Corporate communication in practice -- Chapter 6. Communication strategy and strategic planning -- Chapter 7. research and measurement -- Part IV. Specialist areas in corporate communications -- Chapter 8. Media relations -- Chapter 9. Employee communication -- Chapter 10. Issues management -- Chapter 11. Crisis communication -- Part V. New developments in corporate communication -- Chapter 12. Leadership and change communication -- Chapter 13. Corporate Social Responsibility (CSR) and community relations.
Keywords: Communication in management; Business communication